Snowdrift modeling in a wind-tunnel: vertical and horizontal variation of snow flux - Naaim Bouvet, F.; Naaim, M. (HAL CCSD, 1998)
International audience This paper deals with the influence of the vertical and horizontal variation of aeolian snow flux on estimations of snow-storm duration and on snowdrift patterns simulated in wind-tunnel. First of all, we shall review recent developments, including our own simulations, concerning the horizontal increase of mass-flux until drifting snow saturation has been reached. Next, after a critical examination of various snowdrift modelling criteria, we present the results of an experiment undertaken in our wind-tunnel: we studied cross-section drift-area changes behind a small-scale snow fence as afunction of time for different fetches but for the same mean wind speed at the beginning of the testing section. For each fetch, we carried out vertical profiles of sand particles using image processing and we studied the geometrical parameters of the drift. We conclude that changes in the cross-section drift area depend on the ablation length and if particle saturation is not reached, the use of storm-duration scale leads to overevaluation of prototype storm duration. Moreover, we point out that drift pattern vary as a function of concentration profiles. Cet article traite de l'influence de la variation verticale et horizontale du transport éolien de la neige sur les estimations de durée de la tempête de neige et les schémas de transport de la neige simulés en soufflerie. Premièrement, nous passerons en revue les récents développements, y compris nos propres simulations concernant l'augmentation horizontale de la masse-transport jusqu'à ce que la saturation de la neige transportée ait été atteinte. Puis, après un examen critique des différentes critères de modélisation du transport de la neige, nous présentons les résultats d'une expérience menée dans notre soufflerie : nous avons étudié les changements de transport de section transversale derrière une petite barrière de neige servant d'échelle temporelle pour différentes distances mais pour la même vitesse du vent au début de la section d'essai. Pour ...